2019
DOI: 10.1002/jor.24567
|View full text |Cite
|
Sign up to set email alerts
|

Mitoprotective therapy prevents rapid, strain‐dependent mitochondrial dysfunction after articular cartilage injury

Abstract: Posttraumatic osteoarthritis (PTOA) involves the mechanical and biological deterioration of articular cartilage that occurs following joint injury. PTOA is a growing problem in health care due to the lack of effective therapies combined with an aging population with high activity levels. Recently, acute mitochondrial dysfunction and altered cellular respiration have been associated with cartilage degeneration after injury. This finding is particularly important because recently developed mitoprotective drugs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 63 publications
4
35
0
Order By: Relevance
“…16,17 While mitochondrial repolarization is possible, prolonged depolarization past an unknown threshold of time leads to mitochondrial damage and depending on the severity can induce cell death by apoptosis or necrosis if the damage is extensive. 18,19 While there are promising new chemical interventions to halt the progression of mitochondrial and other biochemical processes, 20,21 the current standard of care is to prescribe rehabilitation therapy to improve supporting musculature strength, joint functionality, and decrease pain. [22][23][24] It is unknown, however, if movement soon after joint injury is beneficial or detrimental to long-term outcome and the development of PTOA.…”
mentioning
confidence: 99%
“…16,17 While mitochondrial repolarization is possible, prolonged depolarization past an unknown threshold of time leads to mitochondrial damage and depending on the severity can induce cell death by apoptosis or necrosis if the damage is extensive. 18,19 While there are promising new chemical interventions to halt the progression of mitochondrial and other biochemical processes, 20,21 the current standard of care is to prescribe rehabilitation therapy to improve supporting musculature strength, joint functionality, and decrease pain. [22][23][24] It is unknown, however, if movement soon after joint injury is beneficial or detrimental to long-term outcome and the development of PTOA.…”
mentioning
confidence: 99%
“…These studies once again show that mitochondrial function is critical for maintenance of cellular energy production via the gradient created in the ETC in joint tissues. Pathogenic unfolding of membrane cristae and loss of membrane polarisation are characteristic of diseases in many tissues, but it is interesting to note that the same has recently been shown to be true in OA (76). These studies also support the potential application of antioxidants and targeting chondrocyte mitochondrial metabolism after injury to mediate PTOA and promote healthy cartilage (75).…”
Section: Mechanobiological Responses Are Linked To Inflammation and Mitochondrial Dynamicsmentioning
confidence: 62%
“…Mechanotransduction is known to influence chondrocyte function. Specifically, studies have demonstrated strain-dependent mitochondrial dysfunction (41, 59) and ROS release (60) in chondrocytes. As several of the proposed mechanisms for active mtDNA release occur in response to mitochondrial dysfunction and increased ROS production (26, 29, 30) , mechanotransduction may represent an important link between mechanical injury and active mtDNA release.…”
Section: Discussionmentioning
confidence: 99%